Study on Mapping of Information Literature Culture in South Coastal Communities West Java Province - Rachmawati, Tine Silvana; Winoto, Yunus; Rohman, Asep Saeful (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2018)
This study aims to mapping the culture of information literacy on coastal communities in West Java region. While the urgency of this research is an effort to foster interest in reading the community, including in this case the people in the coastal areas should be the attention of all parties. The research method used in this study is the mix method (mix method) as a combination approach as an alternative to the use of a single method in a study. The mixed method will give better results because it has a wealth of data, because it can combine or combine. Based on the results of research conducted in the first stage it is known that the culture literasi community in the coastal area in general is still low. In addition, also support the regulation and legislation of local government or district government in the south coast of West Java, namely Sukabumi, Cianjur, Garut, Tasik and Pangandaran) in the effort to develop the culture of literasi in general is still low.